Nivel de conocimiento sobre salud sexual - reproductiva y riesgo a embarazo en adolescentes. LA ESPERANZA 2016 - Fernández Boy, Kelly Yudit (2016)
The following research is a cross section correlational descriptive one. It was carried out during March, 2016 at “Divino Maestro” School in La Esperanza District, which aims to determine the relation between the knowledge level on sexual-reproductive health and the risk of pregnancy in female adolescents. The sample and the universe were constituted by 81 adolescents selected according to established criteria of inclusion. For the information compilation “The questionnaire of Knowledge level on sexual-reproductive adolescents” (QKLSRA) and “The Survey of Risk Adolescent Pregnancy” (SRAP) were used. The results show that 50,6 per cent present an average knowledge, 9,9 per cent have low knowledge level and 72,4 per cent reveal a low risk follow by 27,6 percent with a high risk to pregnancy, relationship between the variables was not significant with a X2 = 6.452 and a value p= 0,0397, and as a result, it was easy to conclude that there is a connection between both variables.